Andreev-spectroscopy study of unconventional superconductivity in MgB₂:(La,Sr)MnO₃ nanocomposite - Krivoruchko, V.N.; D’yachenko, A.I.; Tarenkov, V.Yu. (Физика низких температур, 2014)
Unconventional high-temperature superconductivity in MgB₂:La₀:₆₅Sr₀:₃₅MnO₃ (MgB:LSMO) nanocomposite
has been found recently [Phys. Rev. B 86, 10502 (2012)]. In this report, the symmetry of the nanocomposite
superconducting order parameter and plausible pairing mechanisms have been studied by the point-contact
Andreev-reflection (PCAR) spectroscopy. To clarify the experimental results obtained, we consider a model
of a ferromagnetic superconductor, which assumes a coexistence of itinerant ferromagnetism and mixed-parity
superconductivity. The Balian–Werthamer state, with quasiparticle gap topology of the same form as that
of the ordinary s-wave state, fits the experimental data reasonably well. Utilizing the extended Eliashberg formalizm,
we calculated the contribution of MgB₂ in the total composite’s conductivity and estimated the magnitude
of the electron–phonon effects originated from MgB₂ in I–V characteristics of the composite at above-gap
energies. It was found that distinctive features observed in the PC spectra of the MgB:LSMO samples and conventionally
attributed to the electron–phonon interaction cannot be related to the MgB₂ phonons. It is argued that
the detected singularities may be a manifestation of the electron-spectrum renormalizations due to strong
magnetoelastic (magnon–phonon) interaction in LSMO.